2016
DOI: 10.4236/ojvm.2016.61002
|View full text |Cite
|
Sign up to set email alerts
|

A Survey for Contagious Caprine Pleuropneumonia in Agago and Otuke Districts in Northern Uganda

Abstract: Background: Contagious Caprine Pleuropneumonia (CCPP) is a devastating disease of goats caused by Mycoplasma capricolum subsp. Capripneumoniae (Mccp). The disease was first confirmed in Uganda in 1995 in Karamoja region. Contagious Caprine Pleuropneumonia negatively impacts on goats' productivity but its extent and magnitude among the local communities in Uganda remain unknown. A cross sectional study was conducted in the districts of Agago and Otuke neighboring Karamoja in Northern Uganda during the months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
(29 reference statements)
4
12
2
Order By: Relevance
“…Hadush et al (2009) also reported higher prevalence as 38.6% and 43.9% from Afar and Tigray regions of Ethiopia, respectively. In other parts of the world, higher prevalence than our observation has been documented in Beetal, Pakistan (Shahzad et al 2012), Tanzania (Mbyuzi et al 2014; Nyanja et al 2013), Kenya (Kipronoh et al 2016), Uganda (Atim et al 2016), and Turkey (Cetinkaya et al 2009). An international collaborative study done by Peyraud et al (2014) also reported sero-prevalence of 6 to 90%, 14.6%, 16%, 10.1%, 0%, and (2.7%, 44.2%) from Kenya, Ethiopia, Mauritius, Tajikistan, Afghanistan, and Pakistan, respectively, using monoclonal antibody–based cELISA.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Hadush et al (2009) also reported higher prevalence as 38.6% and 43.9% from Afar and Tigray regions of Ethiopia, respectively. In other parts of the world, higher prevalence than our observation has been documented in Beetal, Pakistan (Shahzad et al 2012), Tanzania (Mbyuzi et al 2014; Nyanja et al 2013), Kenya (Kipronoh et al 2016), Uganda (Atim et al 2016), and Turkey (Cetinkaya et al 2009). An international collaborative study done by Peyraud et al (2014) also reported sero-prevalence of 6 to 90%, 14.6%, 16%, 10.1%, 0%, and (2.7%, 44.2%) from Kenya, Ethiopia, Mauritius, Tajikistan, Afghanistan, and Pakistan, respectively, using monoclonal antibody–based cELISA.…”
Section: Discussionsupporting
confidence: 47%
“…It occurs in many countries in Africa, Asia, and Middle East (Prats-van der Ham et al 2015) and is a classical trans-boundary animal disease (Shahzad et al 2016). Moreover, the disease is included in the list of notifiable diseases of the World Organization for Animal Health (OIE 2008) as it threatens a significant number of goat populations throughout the world and has a considerable socioeconomic impact in infected territories (Atim et al 2016). Though disease is mainly found in goats, subclinical cases were reported in sheep and some wild ruminant species (Asmare et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These findings were consistent with the results recorded by different research works conducted in different areas of Ethiopia [15, 16, 37]. Similarly, higher district level seroprevalences were also reported in Hammer and Benna-Tsemay districts of Southern Ethiopia [37] and Agago and Otuke districts of Uganda [31] with insignificant variation in the occurrence of CCPP. The difference in seroprevalence by districts could be explained by the differences in animal management system with common browsing and watering practices, the frequent animal movement to border regions, and the introduction of new animals.…”
Section: Discussionsupporting
confidence: 91%
“…The study revealed an overall seroprevalence of 8.5% (34 out of 400) in the studied goat population with widespread distribution and varied seropositivity among the study zones and districts. The seroprevalence of CCPP in this study was lower than that in some zones reported by Mekuria and Asmare [29] and Bekele et al [30] in Ethiopia, Atim et al [31] in Uganda, and Ingle et al [32] and Hussain et al [33] in Pakistan. In contrast, the seroprevalence finding in this study was higher than that reported by the same authors in other zones of Ethiopia [30] and in Uganda [31], Pakistan [32], and Turkey [34].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation